Keberadaan Niniak Mamak dalam pertunjukan Ulu Ambek di Korong Pucuang Anam Nagari Tandikek (kajian status, peran dan fungsi) - Windu Okri Harsih; Elida Elida (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
This article aims to reveal and explain the status, role and function of Niniak Mamak in Ulu Ambek Performing arts in Sungai Pucuang Anam Kanagarian Tandikek. This research uses a qualitative approach that is descriptive analysis. Data collection techniques are conducted by observation/observation, literature study, interviews and documentation. Data analysis techniques are conducted with data reduction measures, data presentation and taking conclusions (verification). The results of the research found was that the status of Niniak Mamak was as owner, controller, manager, supervisor, and policy makers from the performances and artistic culture of Ulu Ambek. While the function of Niniak Mamak is as a policy maker and as a planner and as a controller of the show Ulu Ambek.